On the Use of English Adverbial Participle I and its Translation into Lithuanian - Labeikaitė, P. (Kalbotyra, 1976)
According to the syntactical relations in the sentence participles as elements of word-group structure and as elements of sentence structure can be distinguished. Adverbial Participle I can be rendered into Lithuanian by different adverbial participial constructions, adverbial subordinate clauses and co-ordinate clauses. The choice of the means of translation is determined by the grammatical meaning and the lexical character of the participle and by the relation of its agent to the agent of the main action expressed by the finite verb form.